2002
DOI: 10.1063/1.1510665
|View full text |Cite
|
Sign up to set email alerts
|

Unstable ion-temperature-gradient modes in the Wendelstein 7-X stellarator configuration

Abstract: The linear stability of the ion-temperature-gradient modes (ITG) in the electrostatic limit is examined in the short wavelength region by using a two fluid reactive model in fully three-dimensional Wendelstein 7-X (W7-X) stellarator [G. Grieger et al., Plasma Physics and Controlled Nuclear Fusion Research, 1990 (International Atomic Energy Agency, Vienna, 1991), Vol. 3, p. 525] geometry. The spectrum of stable and unstable modes and their real frequencies and eigenfunctions are calculated. The effects of densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 30 publications
6
21
1
Order By: Relevance
“…While the normal curvature in W7-X has strong, fine-scale variations along a magnetic flux tube [14,28], previous work has indicated that due to the fast dynamics parallel to the ambient magnetic field, the averaged normal curvature along a field line dominates the formation and behaviour of turbulent filaments [14,29]. Since the magnetic configurations of W7-X considered here mostly differ with respect to the rotational transform, the magnetic curvature profile along a field line starting from the probe does not change more than a few % between configurations.…”
Section: Magnetic Field Characteristicsmentioning
confidence: 99%
“…While the normal curvature in W7-X has strong, fine-scale variations along a magnetic flux tube [14,28], previous work has indicated that due to the fast dynamics parallel to the ambient magnetic field, the averaged normal curvature along a field line dominates the formation and behaviour of turbulent filaments [14,29]. Since the magnetic configurations of W7-X considered here mostly differ with respect to the rotational transform, the magnetic curvature profile along a field line starting from the probe does not change more than a few % between configurations.…”
Section: Magnetic Field Characteristicsmentioning
confidence: 99%
“…This suggests the stabilizing role of local magnetic shear described in Refs. [15,14]. Comparing Fig.…”
Section: Spatial Structure Of Turbulent Transportmentioning
confidence: 99%
“…Especially in complex stellarator configurations, the local properties of the magnetic field, like curvatures and field-line shear, have to be included into the models in order to describe the structure and dynamics of turbulence appropriately. Different approaches like a ballooning-mode formalism [6,7,8,9,10,11], a full three-dimensional analysis of unstable modes on a flux surface [12,13,14,15] and non-linear fluid [16,17,18] or gyrokinetic [19,4,20,21] simulations point to significant effects of the local magnetic field geometry on the spatial structure and the stability of drift modes. Theoretical studies indicate that turbulent transport can be reduced by more than a factor of 2 if an appropriate shaping procedure considering local magnetic field properties is applied [22].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies of ITG instabilities for tokamaks and a few for stellarators (see, e.g. [10,11]), using fluid or gyrokinetic approaches based on the ballooning approximation. While the ballooning approximation offers a computationally fast and easy way to gain some insight into the dependence of the growth rate on physical parameters and to extend the physical set of equations, it is, nevertheless, only a local calculation performed for each field line which (in its simplest form) gives only very restricted information on the real spatial structure of a mode.…”
Section: Introductionmentioning
confidence: 99%